Traffic-Driven Implicit Buffer Management - Delay Differentiation without Traffic Contracts - Karsten, Martin; Berger, Daniel S.; Schmitt, Jens (2016 International Teletraffic Congress, 2016)
Different network applications have different service preferences regarding packet delay and buffering. Delay management requires scheduling support at routers, which traditionally also requires some form of traffic specification and admission control. In contrast, this paper studies the problem of guaranteeing queueing delay bounds for multiple service classes without traffic contracts and without affecting the throughput rate for each class. A solution to this problem is given by decoupling throughput and delay management via traffic-driven implicit buffer management. Using this concept, the Delay Segment FIFO (DSF) packet scheduler guarantees differentiated delay targets in the presence of unregulated throughput rates. This decoupling represents a modular approach and DSF embodies a small and self-contained feature set. Furthermore, DSF's service model satisfies even a strict interpretation of network neutrality, while effectively guaranteeing delay targets for multiple service classes. DSF's design and service characteristics are analyzed mathematically and validated through simulations.